Inorganic salts influence IAA ionization and adventitious rhizogenesis in Pongamia pinnata - Ansari, Shamim Akhtar; Singh, Sanjay; Rani, Abha (Journal of plant physiology, 2004)
The basal cut end of coppice shoot cuttings of Pongamia pinnata was treated for 24 h with 0 (water treated control) or 5.0 mmol/L of KMnO 4, KCl, and KH 2PO 4 or 2.5 mmol/L of K 2HPO 4 and K 2SO 4. Inorganic salts of P, S, Cl and Mn significantly influenced IAA ionization and adventitious rhizogenesis. P and S salts had lower IAA ionization potential, but more pronounced effect on adventitious rhizogenesis than Cl and Mn salts. The linear regression analysis also established negative correlations between salt induced IAA ionization with various characteristics of adventitious rhizogenesis such as sprouting (r = -0.83, p < 0.05), rooting (r = -0.82, p < 0.05), root number (r = -0.95, p < 0.01), and root length (r = -0.80, p < 0.1). The implication of IAA ionization in adventitious rhizogenesis has been discussed and the possible role of inorganic salts therein suggested.